Sol-Gel Synthesis, X-Ray Diffraction Studies, and Electric Conductivity of Sodium Europium Silicate - Ekaterina V. Borisova; Alexey V. Ignatov; Eugeni I. Get'man; Stanislav N. Loboda; Lyudmyla I. Ardanova; Lyudmila V. Pasechnik; Vitaly S. Ponurovsky (Journal of Chemistry)
Sodium europium silicate, NaEu9(SiO4)6O2, with apatite structure has been obtained and studied using X-ray diffraction and SEM. It has been shown that sodium sublimation does not take place upon synthesis by the sol-gel method. Rietveld refinement has revealed that sodium atoms are ordered and occupy the 4f position. O(4) atoms not related to silicate ions are placed at the centers of Eu(2) triangles. DC and AC electric conductivity and activation energy have been determined for the compound studied.